أثر الترويج في تسويق خدمات النقل الجوي نموذج: مؤسسة الطيران العربية السورية - ديوب, محمد عباس; برهوم, أديب; بركات, نغم منير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعد قطاع النقل الجوي قطاعاً خدمياً هاماً، وله خصائص عديدة يتميز بها عن وسائل النقل الأخرى، وانطلاقاً من أهمية التسويق بشكل عام والترويج بشكل خاص في مؤسسات النقل الجوي، فإن البحث يتناول الترويج، وتسويق خدمات النقل الجوي، كما يركز البحث بشكل خاص على دراسة العلاقة ما بين الترويج وعدد المسافرين جواً، وأهمية وجود إدارة خاصة بالترويج في مؤسسات النقل الجوي وذلك بهدف الترويج للمؤسسة وللخدمات التي تقدمها، والتعرف على حاجات المسافرين المختلفة، ثم العمل قدر الإمكان على تقديم أفضل الخدمات التي تلبي تلك التطلعات والحاجات، وهذا ما قد يساهم بدوره في جذب أكبر عدد ممكن من المسافرين، وتحسين المركز التنافسي لمؤسسة الطيران العربية السوريةعلى الصعيدين العربي والعالمي. وقد توصلت الدراسة إلى مجموعة من النتائج أهمها: - عدم اهتمام مؤسسة الطيران العربية السورية بالتسويق وبالترويج. - عدم وجود علاقة ارتباط بين مخصصات الترويج وزيادة حجم الركاب. - عدم الاهتمام الكافي باختيار العناصر التي تعمل في قسم الترويج والأقسام الخدمية المساعدة. The aerial transport sector is an important one servicewise. It has many characteristics which make it far better than other means of transport. Given the importance of marketing in general and promotion of aerial transport establishments in particular, this study discusses the promotion and marketing of aerial transport services. In particular, it focuses on the relation between promotion and the number of travellers by air as well. It also considers the importance of having a specific administration handling promotion in the aerial transport establishments, aiming to promote the establishment and the services it provides, attend to the passengers' different needs, and provide the best services possible, which fulfill those aspirations and needs; this, in turn, will contribute to attracting the highest number of passengers possible and improving the competitive role of the Syrian Arab Airlines Establishment both nationally and internationally This study has achieved many results, and the most important of which are the following: - No attention being paid to marketing and promotion in the Syrian Arab Airlines Establishment. -There is no correlation between promotion and the increase in the number of passengers. - No attention being paid to choosing the administration staff working in the promotion department and other service departments.